The reasons of inducement of names in two cases. - Mukhitdinov, R. S. (Journal of Oriental Studies, 2016)
In this article the reasons of inducement of the Arab names in two cases are considered. These reasons can be subdivided into two parts. Part connected with value and part connected with a structure of words.